Competition policy : theory and practice - Motta, Massimo (Cambridge University Press, 2004)
This is the first book to provide a systematic treatment of the economics of antitrust (or competition policy) in a global context. It draws on the literature of industrial organisation and on original analyses to deal with such important issues as cartels, joint-ventures, mergers, vertical contracts, predatory pricing, exclusionary practices, and price discrimination, and to formulate policy implications on these issues. The interaction between theory and practice is one of the main features of the book, which contains frequent references to competition policy cases and a few fully developed case studies. The treatment is written to appeal to practitioners and students, to lawyers and economists. It is not only a textbook in economics for first year graduate or advanced undergraduate courses, but also a book for all those who wish to understand competition issues in a clear and rigorous way. Exercises and some solved problems are provided.